Is there a weekend effect after hip fracture surgery? A study of 74,410 hip fractures reported to the Norwegian Hip Fracture Register - Gjertsen, Jan-Erik; Boutera, Andrea; Dyvik, Eva; Hallan, Geir (Acta Orthopaedica, 2019)
Background and purpose — The term “weekend effect” describes differences in outcomes between patients treated at weekends compared with weekdays. We investigated whether there is a weekend effect for the risk of reoperation and mortality after hip fracture surgery at Norwegian hospitals. Patients and methods — We included data from 76,410 hip fractures in patients 60 years and older reported to the Norwegian Hip Fracture Register (NHFR) between 2005 and 2017. Cox survival analyses with adjustments for age, sex, ASA class, type of fracture, operating method, and waiting time from fracture to surgery were used to calculate the risk of reoperation and death after surgeries performed at weekends compared with surgeries performed on weekdays. Results — The mean age for all patients was 82 years, and 71% were female. 73% of fractures occurred on weekdays (Monday to Friday) and 27% during weekends (Saturday and Sunday). 71% of fractures were operated on a weekday and 29% at a weekend. Slightly increased mortality was observed during the 2 first months after weekend admission with hip fracture (HR 1.08; 95% CI 1.03–1.14). This did not continue in subsequent months, but the initial effect of weekend presentation was still apparent at 1-year follow-up. Further, there was no difference in mortality between patients who were operated at a weekend and patients operated on a weekday. Neither were there any differences in the risk of reoperation between weekday and weekend when comparing day of fracture or day of surgery. Interpretation — Patients who suffered a hip fracture during a weekend had slightly increased mortality in the first 2 months postoperatively. Whether the surgery was done on weekdays or at weekends did not affect mortality or the risk of reoperation.